Assessing the Regional Economic Impacts of Defense Activities – A Survey of Methods - Josselin Droff; Alfredo R. Paloyo (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
Defense activities exercised in a specific region may alter the region's economic performances. An accurate assessment of the potential economic impacts of defense activities within a specific area is therefore a valuable undertaking, especially for regional planners who may want to prepare for changes. The variety in the methodological landscape, counting, among others, input-output models, economic base models, Keynesian regional multipliers, fixed-effects estimators, and casestudy approaches inspired by geography, sociology, or political science may pose a dilemma. In this paper, we detail the historical and theoretical background of each method, as well as select exemplary cases where these methods were successfully or inappropriately applied. By examining old and 'new' methods based on the extant literature in regional economics, we aim to construct a methodological typology that could be extremely valuable to all stakeholders. – – Militärische Aktivitäten in einer Region, z.B. das Vorhandensein eines militärischen Stützpunkts, können einen Einfluss auf die Wirtschaftsleistung dieser Region haben. Eine genaue Analyse der regionalökonomischen Effekte dieser militärischen Aktivitäten ist daher ein nützliches Unterfangen, besonders für regionale Planer, die sich auf mögliche Änderungen vorbereiten möchten. Die Vielzahl der methodischen Ansätze, die für eine solche Analyse genutzt werden können, u.a. Input-Output-Modelle, Exportbasismodelle, Keynesianische Multiplikatorenanalyse, Fixed-Effects-Modelle und durch Geographie, Soziologie oder Politikwissenschaft inspirierte Fallstudien-Ansätze, können ein Dilemma darstellen. In diesem Papier beschreiben wir den historischen und theoretischen Hintergrund jeder Methode und zeigen beispielhaft auf, wann diese Methode erfolgreich oder nicht angemessen angewendet wurde. Durch die Untersuchung alter und 'neuer' Methoden auf Basis der bestehenden regionalökonomischen Literatur haben wir zum Ziel eine Typologie der Methoden zu erstellen, die für alle Interessengruppen von hohem Wert sein kann.
Keywords: O18; R11; R15; 330; defense activities; public planning; regional impact methods